1995
DOI: 10.1203/00006450-199508000-00021
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopmental Quotient of Healthy Term Infants at 4 Months and Feeding Practice: The Role of Long-Chain Polyunsaturated Fatty Acids

Abstract: A direct influence of dietary long-chain polyunsaturated fatty acids (LC-PUFA) on the developmental quotient (DO) of the healthy term infant remains unexplored. To test this hypothesis, we designed a prospective study of three types of diet. 'I'wentynine infants received a LC-PUFA-supplemented formula, 31 received a standard infant formula. and 30 infants were breastfed exclusively. Neurodevelopmental response was measured by the Brunet-LCzine psychomotor development test at 4 mo. The fatty acid status was als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
194
1
3

Year Published

1997
1997
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 314 publications
(203 citation statements)
references
References 24 publications
5
194
1
3
Order By: Relevance
“…The influence of postnatal LCPUFA supply on cognitive function in term infants has been investigated in several supplementation studies (Agostoni et al, 1995(Agostoni et al, , 1997Auestad et al, 2001;Birch et al, 2000;Lucas et al, 1999;Makrides et al, 2000;Scott et al, 1998;Willatts et al, 1998a, b). Some randomized controlled LCPUFA trials in term infants younger than 12 months show a positive influence of dietary LCPUFA on cognitive function, as measured with different methods (Agostoni et al, 1995;Willatts et al, 1998a, b). At 12 months of age, an influence of dietary LCPUFA on cognitive function was not observed (Agostoni et al, 1996;Auestad et al, 2001;Makrides et al, 2000;Scott et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The influence of postnatal LCPUFA supply on cognitive function in term infants has been investigated in several supplementation studies (Agostoni et al, 1995(Agostoni et al, , 1997Auestad et al, 2001;Birch et al, 2000;Lucas et al, 1999;Makrides et al, 2000;Scott et al, 1998;Willatts et al, 1998a, b). Some randomized controlled LCPUFA trials in term infants younger than 12 months show a positive influence of dietary LCPUFA on cognitive function, as measured with different methods (Agostoni et al, 1995;Willatts et al, 1998a, b). At 12 months of age, an influence of dietary LCPUFA on cognitive function was not observed (Agostoni et al, 1996;Auestad et al, 2001;Makrides et al, 2000;Scott et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Some randomized supplementation studies, comparing term infants fed either LCPUFA-enriched formulas or standard artificial formulas, show beneficial effects of LCPUFA supplementation on visual or cognitive development (Agostoni et al, 1995;Birch et al, 1998Birch et al, , 2000Makrides et al, 1995;Willatts et al, 1998a, b). Other studies, however, did not confirm this (Agostoni et al, 1997;Auestad et al, 1997Auestad et al, , 2001Lucas et al, 1999;Makrides et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…In our earlier cross sectional study of breast and formula fed infants where we correlated VEP acuity with erythrocyte phospholipid DHA, the range of erythrocyte DHA values was between 2 and 7% total fatty acids (Makrides et al, 1993). Randomised studies comparing infants fed placebo (no DHA) formulas with those fed DHA supplemented formulas have demonstrated that it is possible to improve erythrocyte DHA levels but have reported con¯icting results (Makrides et al, 1995;Agostoni et al, 1995;Auestad et al, 1997). These studies require careful interpretation since each study has compared a mixture of LCPUFA, from different sources, in a variety of background formula fat blends.…”
Section: Discussionmentioning
confidence: 99%
“…This has been related to the presence of the DHA in breast milk, a fatty acid which is not included in most formulas. The association between dietary DHA and improved retinal and neural outcomes has been veri®ed in both observational studies and randomised trials involving both term and preterm infants (Birch et al, 1992a;Birch et al, 1992b;Makrides et al, 1995;Carlson et al, 1993;Agostoni et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis has shown an approximate 3 IQ-point benefit of breastfeeding when compared to infant formulas [5]. Some randomized supplementation studies, comparing term infants fed formulas enriched with DHA or DHA and n-6 PUFA (arachidonic acid (AA) or gammalinoleic acid) or standard infant formulas, have shown beneficial effects on cognitive development [6][7][8][9], but other studies did not confirm this [10][11][12][13][14]. Furthermore, one study found a transient negative effect on linguistic development in infants supplemented with DHA [11,14].…”
Section: Introductionmentioning
confidence: 99%